Analysis of the Mechanical Properties of Concrete Blocks Reinforced With Glass Particles and Recycled Paper: A Sustainable Approach - Gonzales Saldaña, Jordan Stuar; Tepe Atoche, Victor Manual (International Journal of Sustainable Construction Engineering and Technology, 2024)
The materials to produce concrete blocks (sand, gravel, and cement) are limited resources that are becoming scarce over time due to their increasing demand in construction. On the other hand, the waste of glass and paper is progressively increasing without being fully utilized through recycling. Therefore, the objective of this scientific research is to evaluate the influence on the mechanical properties of masonry concrete blocks made with recycled glass and paper particles. Likewise, the sample was non-probabilistically selected for convenience, consisting of 192 concrete blocks manufactured with additions of 3% (2% glass particles and 1% recycled paper), 6% (4% glass particles and 2% recycled paper), and 9% (6% glass particles and 3% recycled paper), as well as concrete blocks manufactured without additions. According to the results obtained, at 3%, 6%, and 9% addition of glass and paper particles, the absorption decreased by 4.94%, 3.398%, and 3.52% respectively. However, the warping increased between 1.7mm and 1.8mm, while the compressive strength (f’c) increased to 75kg/cm2, 82kg/cm2, and 77kg/cm2, respectively. Similarly, the axial compressive strength (f’m) increased to 91.22kg/cm2, 94.45kg/cm2, and 92.80kg/cm2, and the diagonal compressive strength (V’m) increased by 8.90kg/cm2, 9.70kg/cm2, and 9.70kg/cm2. Nevertheless, the manufacturing cost of masonry units showed a progressive reduction with the amount of glass + paper addition, amounting to 0.57 USD, 0.55 USD, and 0.53 USD. It was also determined that the optimal addition of these materials in the concrete mix in terms of cost and strength is 9% (glass + paper), resulting in compressive strengths of 77kg/cm2, 92.8kg/cm2, and 9.70kg/cm2, with a cost of 0.53 USD per unit. In conclusion, it can be affirmed that adding glass and recycled paper particles in the production of concrete blocks for use in load-bearing masonry walls positively influences the physical and mechanical properties of the blocks. Additionally, it allows for a reduction in manufacturing costs, leading to significant savings for builders.